THE SOVIET-GERMAN NON-AGGRESSION TREATY OF 1939: A STRATEGIC GAIN OR TRAGIC MISTAKE OF THE USSR (ON THE 80TH ANNIVERSARY OF SIGNING THE TREATY) - A. Kudryavtsev (Гуманитарные и юридические исследования)
In the history of the Second World War, the Soviet-German Treaty, signed on August 23, 1939, occupies a special place and for 80 years remains one of the widely discussed and debatable questions of the second half of the 20th - early 21st centuries. Significant differences in understanding the causes and objectives, interested in concluding the agreement of the parties, the interpretation of the results achieved in their course and the admitted strategic miscalculations, remain up to date and controversial both in Russian and in foreign historiography of the Soviet and post-Soviet periods. The Munich "conspiracy", which had the goal of "pacification" in Europe due to the dismemberment and further occupation of a sovereign European country, did not bring the expected results, but sowed fear and doubts in small Eastern European countries. The Soviet Union, not without reason fearing for its security, in the period from March to August 1939, was looking for an opportunity to maintain neutrality, while probing the Anglo-French position on the conclusion of a military-political agreement with the USSR. Long sluggish negotiations in May-August 1939, between Britain, France and the USSR, where the two irst powers sought, above all, to push the Soviet Union with Nazi Germany, shifting the vector of the approaching war to the East, did not produce real results and reached an impasse. Hitler, back in April 1939, who signed the Weiss plan, which, from September 1, 1939, envisaged military measures to defeat and seize Poland, needed an agreement with the USSR that would allow Germany to avoid war on two fronts - in the West and in the East. Stalin, who was afraid of creating a single anti-Soviet front and disbelieved by the sincerity of the Anglo-French proposals by mid-August, saw broader prospects for the security of the Soviet Union and the postponement of the war with Germany, in the opportunity to conclude a non-aggression treaty with it, which German diplomats actively probed with May - June 1939. Germany, which by the twenties had concentrated more than 1.5 million soldiers, about 2,800 tanks and 2,000 airplanes, urgently needed to sign the agreement fall from the USSR. Not wanting to postpone the start of hostilities, Hitler made very signiicant concessions, including questions of a military-political, territorial, economic nature, advanced beforehand in a special telegram sent by him on August 21, sent to Stalin on August 23. In Moscow in 1939 Ribbentrop (German Foreign Minister) and Molotov (head of the USSR NKID) signed a non-aggression agreement and a secret annex to it on the delimitation of spheres of influence and territories between the USSR and Germany "in the area from the Baltic to the Black Sea".